Study on Poultry Coccidiosis in Tiyo District, Arsi Zone, Ethiopia - Gari, Getachew; Tilahun, Getachew; Dorchies, Ph. (International Journal of Poultry Science, 2008)
The objective of this study was first to investigate the prevalence of poultry coccidiosis and to identify the coccidial species occurring in the study area on local strain and Rhode Island Red breed chicken. The study involved questionnaire survey, fecal examination, necropsy examination and identification of coccidial species based on their morphology, predilection site in the intestine and sporulation time. More than 75% respondents indicated that poultry production and income generated from poultry production in the rural community is the major income source for females and youth and bloody diarrhea predominantly appeared during wet season than chalky, yellow or green diarrhea. Public and private veterinary service centers have no anti coccidial drugs and other medicaments used for poultry diseases. Frequency detection of oocyst in the fecal samples from Rhode Island Red breed and local strain chicken was 80.65% and 61.25% respectively. This finding indicated that coccidial infection in Rhode Island Red breed was significantly higher than in local strain chicken (p < 0.05). The lesion score and mean oocyst output per gram feces was also considerably higher in Rhode Island Red breed than in local strain chicken (p < 0.05, p < 0.001 respectively), which may be the difference due to management system and breed. Clinical coccidiosis occurrence in Rhode Island Red breed and local strain chicken was 22.58% and 12.25% respectively. There was no statistically significant difference in clinical coccidiosis occurrence between the two genotype chickens and system. Eimeria species identified in descending order of their occurrence were E. tenella, E. acervulina, E. necatrix, E. maxima and E. mitis. Mixed infections were the predominant in both production systems. E. mitis was diagnosed for the first time in Ethiopia.